Market segmentation analysis to find out products and services that suit customer needs using the python KMEANS clustering method (Case study: Superindo Tambun Area, Bekasi) - Praditya , Rizqy Gumilar; Sembodo, Giri; Heikal, Jerry (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
This study analyzes market segmentation of 1000 Superindo consumers in Tambun, Bekasi, using K-Means Clustering with Python 3.10. Variables included age, gender, occupation, purchase amount, product type, and discounts. Three main segments were identified: "Business Women" (average age 40, focus on staple goods, 16% discount), "Women Government Career" (age 39, staple goods, 16% discount), and "Professional Women" (age 38, staple goods, 15% discount). Superindo should target "Women Government Career" with the highest purchasing power. To increase sales, an online value proposition is recommended offering bundled packages of staple goods with meat and fruit.